Lurbinectedin in small cell lung cancer - Manzo, Anna; Sforza, Vincenzo; Carillio, Guido; Palumbo, Giuliano; Montanino, Agnese; Sandomenico, Claudia; Costanzo, Raffaele; Esposito, Giovanna; Laudato, Francesca; Mercadante, Edoardo; La Manna, Carmine; Muto, Paolo; et al. (Frontiers in Oncology, 2022)
Patients with small-cell-lung cancer (SCLC) in progression after a first line therapy have few treatment options. A novel therapeutic approach is represented by lurbinectedin, a synthetic derivative of trabectedin that inhibits oncogenic transcription and leads to tumor cell apoptosis. A phase II basket trial demonstrated the activity of lurbinectedin at the dose of 3.2 mg/m2 in patients with SCLC who had failed a previous chemotherapy, with a response rate of 35.2%, a median progression-free survival was 3.5 months and a median overall survival was 9.3 months. Common grade 3–4 adverse events were haematological disorders, including anaemia (9%), leucopenia (29%), neutropenia (46%) and thrombocytopenia (7%). On the basis of the positive results of this phase II study, on June 15, 2020 the Food and Drug Administration granted accelerated approval to lurbinectedin for patients with SCLC in progression on or after platinum-based chemotherapy. Unfortunately, the subsequent phase 3 trial comparing the combination of lurbinectedin plus doxorubicin versus CAV or topotecan failed to demonstrate an improvement in overall survival, although a superior safety profile was showed by the experimental arm. New combinations of lurbinectedin with other cytotoxic agents and immune checkpoint inhibitors are currently under investigation: the results of these studies should better define the optimal clinical application of lurbinectedin.